KONFLIK BATIN TOKOH KAGEYAMA SHIGEO PADA ANIME MOB PSYCHO 100 KARYA YUZURU TACHIKAWA - Adi Putrawan I Gde; Betty Debora Aritonang (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
This research aims to describe and examine the inner conflict experienced by the main character Kageyama Shigeo in the anime Mob Psycho 100. The method used in this research is descriptive qualitative and the data source comes from the anime Mob Psycho 100, the theory of inner conflict developed by Sigmund Freud (1923) will be applied to analyze the data collected in this research. This research uses the listen-and-note method to collect data. And, qualitative descriptive methods are applied to examine data analysis methods and techniques. The results of the research show that the analysis of three structures of inner conflict, namely id, ego, and superego, is used to analyze the inner conflict experienced by the main character Kageyama Shigeo.